Research on QR code logistics privacy based on segmented encryption and time-limited control - Liang LIU; Wenbo GUO; Yuwei YANG; Huaiyu GUO (网络与信息安全学报)
In view of the disadvantages of the existing logistics system in the market in user privacy protection,a privacy protection scheme based on QR code segmentation encryption,hierarchical authorization and time-limited control was proposed.This scheme segments all the recipient information into RSA and Base64 encryption,after integration,it is embedded into the QR code.In the process of logistics transportation and delivery,different levels of QR code decryption permissions are granted to different branches or transfer centers to view the designated content.At the same time,the QR code automatically becomes invalid after the user signs for it,so as to protect the user's privacy.The core idea of the scheme is to minimize the contact group of recipient information and reduce the possibility of user information disclosure.